STUDY OF SOCIO-ECONOMIC STATUS AND KNOWLEDGE LEVEL OF DAIRY FARMERS ABOUT DAIRY TECHNOLOGY - Bankar, PS; Patil, Sneha; Deshmukh, SG (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The study was conducted in Akola district of Maharashtra with 59 dairy farmers to their socio economic status and measure level of knowledge about dairy technology. Socio-economic status of dairy farmers was poor and most of the respondents were observed with average knowledge level regarding dairy technology and from the study it is clear that extension agencies have to be more active to enhance the knowledge level through target oriented extension training programmes.
Keywords: Socio-economic status; Knowledge level; Dairy farmer; Dairy technology; Rural